The telomere binding protein Pot1 maintains haematopoietic stem cell activity with age. Issue 1 (December 2017) - Hosokawa, Kentaro; MacArthur, Ben; Ikushima, Yoshiko; Toyama, Hirofumi; Masuhiro, Yoshikazu; Hanazawa, Shigemasa; Suda, Toshio; Arai, Fumio
Abstract Repeated cell divisions and aging impair stem cell function. However, the mechanisms by which this occurs are not fully understood. Here we show that protection of telomeres 1A (Pot1a), a component of the Shelterin complex that protects telomeres, improves haematopoietic stem cell (HSC) activity during aging. Pot1a is highly expressed in young HSCs, but declines with age. In mouse HSCs, Pot1a knockdown increases DNA damage response (DDR) and inhibits self-renewal. Conversely, Pot1a overexpression or treatment with POT1a protein prevents DDR, maintained self-renewal activity and rejuvenated aged HSCs upon ex vivo culture. Moreover, treatment of HSCs with exogenous Pot1a inhibits the production of reactive oxygen species, suggesting a non-telomeric role for Pot1a in HSC maintenance. Consistent with these results, treatment with exogenous human POT1 protein maintains human HSC activity in culture. Collectively, these results show that Pot1a/POT1 sustains HSC activity and can be used to expand HSC numbers ex vivo. Repeated cell divisions induce DNA damage in haematopoietic stem cells (HSC) and telomeres are sensitive to this damage. Here, the authors show in murine HSCs that the telomere binding protein POT1a inhibited the production of reactive oxygen species, and rejuvenated aged HSCs.